2015
DOI: 10.1016/j.jvs.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes of vascular reconstruction in soft tissue sarcomas of the lower extremities

Abstract: Arterial and venous reconstruction is feasible after surgical resection of lower limb STS. Vascular reconstruction provides favorable long-term patency outcomes and low complication rates, allowing limb preservation and disease control in a select group of patients. Vascular reconstruction using venous grafts had a significantly higher patency rate than reconstruction with artificial venous substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 15 publications
(10 reference statements)
3
21
1
Order By: Relevance
“…However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral. In this review, only two small comparative studies without uniform follow‐up protocol reported an overall limb‐salvage rate between autologous and synthetic graft; one study reported that vascular reconstruction using autologous graft had a significantly higher patency rate than reconstruction with synthetic graft in their 25 patients (Nishinari et al, ); however, the other study suggested no significant differences between the graft materials in their 14 patients (Schwarzbach et al, ). The impact of graft material selection on limb‐salvage rate remains unclear in the current data set; therefore, it is necessary to compare the long‐term results between the graft materials with a randomized control trial or large prospective study before any definitive statement can be made.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in sarcoma surgery in contrast to obstructive arterial disease, there are some specific situations, such as requirement of a relatively short graft, not atherosclerotic artery, and postoperative formation of arterial collateral. In this review, only two small comparative studies without uniform follow‐up protocol reported an overall limb‐salvage rate between autologous and synthetic graft; one study reported that vascular reconstruction using autologous graft had a significantly higher patency rate than reconstruction with synthetic graft in their 25 patients (Nishinari et al, ); however, the other study suggested no significant differences between the graft materials in their 14 patients (Schwarzbach et al, ). The impact of graft material selection on limb‐salvage rate remains unclear in the current data set; therefore, it is necessary to compare the long‐term results between the graft materials with a randomized control trial or large prospective study before any definitive statement can be made.…”
Section: Discussionmentioning
confidence: 97%
“…Anticoagulation therapy followed by vascular reconstruction was reported in 14 studies (Adelani et al, 2007;Akgül et al, 2018;Baxter et al, 2007;Bonardelli et al, 2000;Emori et al, 2012;Ghert et al, 2005;Kawai et al, 1996;Koperna et al, 1996;Muramatsu et al, 2011;Nishinari et al, 2015;Schwarzbach et al, 2005;Spark et al, 2009;Tsukushi et al, 2008;Umezawa et al, 2013). Use of anticoagulation regimens varied widely across the studies, with 10 studies reporting intraoperative and postoperative use of heparin or lowmolecular-weight heparin.…”
Section: Reconstructive Proceduresmentioning
confidence: 99%
“…Graft occlusion rates were found to be significantly greater in patients who received synthetic grafts vs. those who received saphenous vein grafts (P = 0.02), which is consistent with the results of other studies [14] . However occlusion rates were not different between arterial and venous reconstruction and there was no association between prior radiotherapy and graft occlusion [44] . Wortman et al [45] reported one-year patency rates of venous bypass grafts to be 65%, with high numbers of overall bypass-related complications including thrombosis and emboli as well as infections.…”
Section: Vascular Reconstructionmentioning
confidence: 74%
“…Studies showing high occlusion rates have led to debates regarding the benefits of venous revascularization [43] . Additionally, there have been reports of symptoms of severe venous insufficiency such as edema, claudication, and hyperpigmentation after reconstruction [44] .…”
Section: Vascular Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation